Local Power in the Japanese State. - Muramatsu, Michio (Berkeley : University of California Press, 2021)
This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1997.
Intro -- Contents -- Illustrations -- Tables -- Preface to English Edition -- Preface to Original Edition -- CHAPTER I. A Sketch of Postwar Local Government -- CHAPTER 2. Central-Local Relations -- CHAPTER 3. The Changing Role of the Prefectures -- CHAPTER 4. The Municipalities -- CHAPTER 5. A Reexamination of the Concept of Local Government -- CHAPTER 6. The Overlapping Authority Model of Central-Local Relations -- Epilogue -- Bibliography -- Index
Description based upon print version of record.
JSTOR
Keywords: Local government -- Japan; Central-local government relations -- Japan; Local government; Central-local government relations; Administration locale -- Japon; Relations gouvernement central-collectivités locales -- Japon; Administration locale; Relations gouvernement central-collectivités locales; local government; Central-local government relations; Local government; Japan